Effect of Immobilization Towards Thermal Stability of a-Amylase Isolated from Locale Bacteria Isolate Bacillus subtilis ITBCCB148 with Calcium Alginate - Yandris; Amalia, Putri; Suhartati, Tati; Hadi, Sutopo (Asian Journal of Chemistry, 2013)
The research aims to increase the thermal stability of enzyme of a-amylase obtained from local bacteria Bacillus subtilis (ITBCCB148) using immobilization process with entrapment method using alginate as the immobile matrix. To achieve this aim, the purification of enzyme was performed on the following phases: fractionation with ammonium sulphate, dialysis and colomn chromatography with CM-cellulose. The result showed that the native enzyme which has been purified has optimum temperature of 55 ºC. The thermal stability test at 60 ºC for 1 h, the native enzyme has residual activity of 3 %, t1/2 = 11 min, ki = 0.063 min-1 and DGi = 100.859 kJ mol-1; while for the immobilized enzyme the values obtained were residual activity of 68 %, t1/2 = 115.5 min, ki = 0.006 min-1 and DGi = 107.369 kJ mol-1. The optimum temperature of immobilized enzyme was 60 ºC. The thermal stability of the imobilized enzyme was 10.5 times compared to the native enzyme. On repeating use, the immobilized enzyme was able to be used 4 times.